A non‐equal gap distance dielectric barrier discharge: Between cone‐shape and cylinder‐shape electrodes. (19th June 2021) - Jin, Shaohui; Li, Zhiyu; Xian, Yubin; Nie, Lanlan; Lu, Xinpei
Abstract: A non‐equal gap distance dielectric barrier discharge (DBD) between cone‐shape and a cylinder‐shaped electrodes is reported. The DBD is driven by a nanosecond voltage pulse. When the pulse frequency is 500 Hz or lower, ladder‐shape plasma with multiple plasma layers is generated within the gap, with a distance increasing from 1 to 7 mm. According to high‐speed photographs of the plasma captured by an intensified charge‐coupled camera detector camera, the ladder‐shaped plasma is formed owing to propagation of ring‐shaped plasma from the region of the short‐gap distance to the region of long‐gap distance with regular variations in its propagation speed. The propagation speed drops to zero and lasts for about 20–30 ns at the region of each plasma layer, which results in bright plasma layers. The electric field of the plasma layer at the region of the different gap distance is evaluated according to the optical emission intensity ratio R 391/394 of N2 + at 391 nm and N2 at 394 nm. The obtained electric field drops from 8.1 to 6.4 kV/mm when the plasma is propagated from regions of gap distance of 2–5 mm. When the pulse frequency is increased to 1 kHz or higher, the discharge changes into a filamentary mode and the multiple‐layer plasma disappears.